Influence of cognitive performance on musculoskeletal injury risk: a systematic review - Avedesian, J. M.; Forbes, W.; Covassin, T.; Dufek, J. S. (The American Journal of Sports Medicine, 2021)
Background: While a large number of studies have investigated the anatomic, hormonal, and biomechanical risk factors related to musculoskeletal (MSK) injury risk, there is growing evidence to suggest that cognition is an important injury contributor in the athletic population. A systematic review of the available evidence regarding the influence of cognitive performance on MSK injury risk has yet to be published in the sports medicine literature.